Penggunaan Instagram sebagai Media Komunikasi - Vira Indar Nevyra; Sori Monang; Abdul Karim Batubara (Medan Resource Center, 2021)
This article aims to describe and explain how the use of the Instagram application is used as a medium of interaction and communication. The problem is focused on the use of Instagram as a communication medium, the weaknesses and strengths of Instagram as a communication medium, and the impact of using Instagram on the social life of students. In order to approach this problem, the uses and gratifications theory is used as a reference. The data was collected through observations of students' Instagram accounts, in-depth interviews with students with Instagram accounts, and documenting student activities on Instagram. The results show that Instagram has advantages and disadvantages, as well as positive and negative impacts. The positive impact of using Instagram for students is that they gain a lot of insight and information, make users creative, can see the outside world through photos and videos, can meet old friends and new people around the world, and provide many benefits for business actors. Meanwhile, the negative impact that is felt is to make Instagram addicted and wasteful in using the internet.